1978
DOI: 10.1159/000260344
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Caries-Like Lesions Created in vitro in Fluorosed and Sound Enamel

Abstract: The acidified-gel artificial caries technique has been used to produce in vitro caries-like lesions in fluorosed and sound enamel. Both abraded and unabraded surfaces were exposed to attack. Results showed that the histological features were similar in fluorosed and non-fluorosed specimens, although the pore volumes in the body of the lesion were much less in fluorosed specimens despite their initial porosity. Where the surface was abraded, greater depth of lesion penetration was noted with no intact surface z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…It thus appears that with increasing severity of fluorosis the tissue becomes re markably resistant to the artificial carious process in accordance with our previous ob servations [ Kidd et al, 1978], Whether the increased resistance of the enamel developed in a high fluoride area to an artificial caries like attack should be related to the high fluoride content of the tissue or its increased protein content, or both, is at present un known and warrants further investigation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It thus appears that with increasing severity of fluorosis the tissue becomes re markably resistant to the artificial carious process in accordance with our previous ob servations [ Kidd et al, 1978], Whether the increased resistance of the enamel developed in a high fluoride area to an artificial caries like attack should be related to the high fluoride content of the tissue or its increased protein content, or both, is at present un known and warrants further investigation.…”
Section: Discussionsupporting
confidence: 86%
“…On removal from the gel, the first longitudinal ground section was prepared from each specimen. Qualitative and quantitative imbi bition studies were carried out in polarized light [Kidd et al, 1978]. The histological examination was arranged so that the examiners did not know the fluoride content of the enamel surface as mea sured before the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical and structural changes of primary and perma nent teeth exposed to increased fluoride during tooth development have been de scribed in detail Thylstrup, 1978;, More fluoride has been found in the surface enamel of such teeth [Jenkins and Speirs, 1953;Isaac et al, 1958;Kidd et al, 1980] and more recently increased con centrations of fluoride have been reported also in the inner bulk enamel from fluo rosed teeth [Lex, 1974;Richards et al, 1979], Experiments in our laboratories have suggested that highly porous fluorosed en amel may be less susceptible to artificial caries [Kidd et al, 1978[Kidd et al, , 1980, In an attempt to improve our knowledge of how fluoride interacts with caries devel opment and apply the experience gained by our in vitro observations, the aim of the present paper is to report on differences in histological features of early carious lesions in fluorosed and non-fluorosed deciduous teeth. As previously mentioned, the histo pathology of the carious deciduous enamel is well known and as the findings in our control specimens did not differ from that previously reported, only specimens from fluorosed teeth will be shown.…”
mentioning
confidence: 99%
“…Based on available enamel biopsy data from fluori dated communities [Aasenden et al, 1971;Larsen et al, 1972], Moreno et al [1971] concluded that a fluoride concentration of approximately 2,500 ppm typically found in the enamel surface at a depth of 2 ¡im, assuming the enamel surface to be a ho mogeneous FHA, would correspond to a 7% degree of OH substitution; an amount which should not significantly affect ob served solubility. Experimentally, it has indeed been found that such small amounts of fluoride present in enamel do not substantially alter enamel solubility [Brudevold and McCann, 1968], and it has been suggested from in vitro studies [Kidd et al, 1978] that the cariostatic effect of fluoride in optimally fluoridated areas may well be a result of its topical effect. Thus, reduced solubility of the enamel sur face can not alone account for the known cariostatic effect of fluoride.…”
Section: Resultsmentioning
confidence: 99%